2018
DOI: 10.1002/lsm.23036
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of poikiloderma of Civatte using a redesigned pulsed dye laser with a 15 mm diameter treatment spot

Abstract: Objectives The pulsed‐dye laser has long been a gold standard in the treatment of poikiloderma of Civatte. Recent advances in pulsed dye laser technology enable output energies 50% higher, enabling beam diameters of up to 15 mm with clinically relevant fluences. In this study, we investigate this new laser for treatment of this condition. Materials and Methods Twenty subjects were enrolled in the study. A total of four treatments were administered at monthly intervals. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 11 publications
0
15
0
1
Order By: Relevance
“…It is very important to relieve these side effects, especially in the young population. Topical corticosteroids have been used to decrease the inflammatory response and prevent scarring (Bernstein, Schomacker, Paranjape, & Jones, 2019;Gao et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is very important to relieve these side effects, especially in the young population. Topical corticosteroids have been used to decrease the inflammatory response and prevent scarring (Bernstein, Schomacker, Paranjape, & Jones, 2019;Gao et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…It is very important to relieve these side effects, especially in the young population. Topical corticosteroids have been used to decrease the inflammatory response and prevent scarring (Bernstein, Schomacker, Paranjape, & Jones, ; Gao et al, ). Nd YAG lasers are also an important treatment option as they can affect the deep vascular structures of PWSs (Wang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…None of the patients developed scarring due to the laser treatment and the treatment response was slower in the neck region compared to the facial region. Hereby, Bernstein et al suggested that PDL was an effective and safe treatment method for poikiloderma of Civatte 9 . However, in another study, it was reported that hypopigmentation and atrophic scars developed in the neck region after treatment with PDL.…”
Section: Discussionmentioning
confidence: 99%
“…Hereby, Bernstein et al suggested that PDL was an effective and safe treatment method for poikiloderma of Civatte. 9 However, in another study, it was reported that hypopigmentation and atrophic scars developed in the neck region after treatment with PDL. The authors recommended being careful when using PDL in the neck area.…”
Section: F I G U R Ementioning
confidence: 96%
“…Ultimately, the best treatments should make people healthier and in turn happier, with improved quality of life. Treatment of Poikiloderma of Civatte using a redesigned pulsed dye laser with a 15 mm diameter treatment spot was evaluated by Bernstein et al, reminding us that we can continue to improve on light‐based technologies, even one of the oldest and best, the pulsed dye laser (https://onlinelibrary.wiley.com/doi/10.1002/lsm.23036). In addition, Aria Vazirnia and Arisa Ortiz from the University of California, San Diego describe treatment of benign pigmented lesions using a novel dermal cooling system which provides precise skin freezing (https://onlinelibrary.wiley.com/doi/10.1002/lsm.23037).…”
mentioning
confidence: 99%